Web-based cognitive behavioural therapy blended with face-to-face sessions for chronic fatigue in type 1 diabetes: a multicentre randomised controlled trial. Issue 6 (June 2017) - Menting, Juliane; Tack, Cees J; van Bon, Arianne C; Jansen, Henry J; van den Bergh, Joop P; Mol, Marc J T M; Goedendorp, Martine M; Donders, Rogier; Knoop, Hans
Summary: Background: Fatigue in type 1 diabetes is prevalent and persistent, but so far, no evidence-based treatments are available. We aimed to investigate the efficacy of cognitive behavioural therapy (CBT) in reducing fatigue severity in patients with type 1 diabetes. Methods: We did a multicentre randomised controlled trial at one university medical centre and four large teaching hospitals in the Netherlands. Eligible patients were aged 18–70 years and had type 1 diabetes for at least 1 year and chronic fatigue for at least 6 months. We randomly assigned patients (1:1) to CBT or waiting list using computer-generated blocked randomisation, stratified by type of enrolment. The CBT intervention (Dia-Fit) was given for 5 months in blended form, consisting of face-to-face and web-based sessions. The primary outcome was fatigue severity assessed 5 months after randomisation, directly after the intervention or waiting list period, with the Checklist Individual Strength fatigue severity subscale. Secondary outcomes were functional impairment (assessed with the total score of the Sickness Impact Profile-8), glycaemic control (HbA1c ), and glucose variability. Analyses were done by intention to treat. This trial is registered with the Nederlands Trial Register, number NTR4312. Findings: Between Feb 6, 2014, and March 24, 2016, we randomly assigned 120 eligible patients to either CBT (n=60) or waiting list (n=60), all of whom were included in the intention-to-treat analyses. Compared with patients in the waiting list group, those in the CBT group had significantly lower fatigue severity scores (mean difference 13·8, 95% CI 10·0–17·5; p<0·0001) and significantly lower scores for functional impairment (mean difference 513, 95% CI 340–686; p<0·0001) after 5 months. HbA1c and glucose variability did not change after treatment and there was no difference between groups. Five patients in the CBT group and seven in the waiting list group reported adverse events; none were deemed to be related to the study intervention. Interpretation: Although our findings need to be confirmed in larger and longer-term studies, they suggest that CBT can effectively reduce fatigue severity and functional impairment in type 1 diabetes. Funding: Dutch Diabetes Research Foundation (Diabetes Fonds).